2015
DOI: 10.1007/978-3-319-16865-4_7
|View full text |Cite
|
Sign up to set email alerts
|

Learning Detectors Quickly with Stationary Statistics

Abstract: Abstract. Computer vision is increasingly becoming interested in the rapid estimation of object detectors. The canonical strategy of using Hard Negative Mining to train a Support Vector Machine is slow, since the large negative set must be traversed at least once per detector. Recent work has demonstrated that, with an assumption of signal stationarity, Linear Discriminant Analysis is able to learn comparable detectors without ever revisiting the negative set. Even with this insight, the time to learn a detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
(54 reference statements)
1
2
0
Order By: Relevance
“…We found that it was important to provide the Correlation Filter with a large region of context in the training image, which is consistent with the findings of Danelljan et al [8] and Kiani et al [16]. To reduce the effect of circular boundaries, the feature map x is pre-multiplied by a cosine window [4] and the final template is cropped [30].…”
Section: Correlation Filter Networksupporting
confidence: 86%
“…We found that it was important to provide the Correlation Filter with a large region of context in the training image, which is consistent with the findings of Danelljan et al [8] and Kiani et al [16]. To reduce the effect of circular boundaries, the feature map x is pre-multiplied by a cosine window [4] and the final template is cropped [30].…”
Section: Correlation Filter Networksupporting
confidence: 86%
“…This implies that each component is a member of a set of structured matrices, M l . This structure could be, but not limited to, block sparse [8], diagonal, Toeplitz or circulant [13], [26] as these structures provide redundancies which enable multiplication to be performed efficiently.…”
Section: A Objective and Structurementioning
confidence: 99%
“…We leverage recent work on rapid estimation of LDA classifiers [3,19] to achieve this goal, though fast correlation filter estimation [4] is potentially equally applicable. The method we present is largely agnostic to the objective used to learn the linear detectors (e.g.…”
Section: Prior Artmentioning
confidence: 99%